Study Produktivitas dan Efisiensi Penebangan Mekanis Tanaman Eucalyptus sp. Di Hutan Tanaman Industri - Santo Wibowo Lumban Gaol; Siman Suwadji; Hastanto Bowo Woesono (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2023)
The use of wood harvesting equipment greatly helps the company to achieve the goals, namely: (1) speed up the process of carrying out work; (2) carrying out the kind of work that cannot be done by human labor; and (3) it is done for reasons of efficiency, limited labor, security and economic factors. Therefore, in order for the goal to be achieved, it is necessary to choose tools that are appropriate, economical and in accordance with working conditions. The selection of inappropriate tools can result in not achieving the expected goals and can cause damage to the tool itself. In the process of logging carried out at PT. RAPP on fully mechanical and semi-mechanical systems uses different logging tools. Each tool in logging activities has its own disadvantages and advantages. So it is necessary to conduct research on comparing the productivity and efficiency of logging using chainsaws and excavator attachment tree shear on Eucalyptus sp plants. Based on the results of the test analysis conducted, the average chainsaw productivity of STIHL MS 382 was 11.32 m³ / hour smaller than the productivity of excavator KOBELCO SK-130 HD with attachman tree shear Dymax 14 In